Rapid Evolution of Autosomal Binding Sites of the Dosage Compensation Complex in Drosophila melanogaster and Its Association With Transcription Divergence - Dai, Aimei; Wang, Yushuai; Greenberg, Anthony; Liufu, Zhongqi; Tang, Tian (Frontiers in Genetics, 2021)
How pleiotropy influences evolution of protein sequence remains unclear. The male-specific lethal (MSL) complex in Drosophila mediates dosage compensation by twofold upregulation of the X chromosome in males. Nevertheless, several MSL proteins also bind autosomes and likely perform functions not related to dosage compensation. Here, we study the evolution of MOF, MSL1, and MSL2 biding sites in D. melanogaster and its close relative D. simulans. We found pervasive expansion of the MSL binding sites in D. melanogaster, particularly on autosomes. The majority of these newly-bound regions are unlikely to function in dosage compensation and associated with an increase in expression divergence between D. melanogaster and D. simulans. While dosage-compensation related sites show clear signatures of adaptive evolution, these signatures are even more marked among autosomal regions. Our study points to an intriguing avenue of investigation of pleiotropy as a mechanism promoting rapid protein sequence evolution.